Experience with managing retrosternal goitres in ibadan, Nigeria (2016)
Background: There is no general consensus on the definition of retrosternal goitre however thyroidectomy remains the gold standard of treatment with or without a sternotomy Aim: To review the outcome of surgical management of retrosternal goitres. Methodology: Retrospective review of records of patients who had thyroidectomy for retrosternal goitre over a 15-year period. Results: Out of a total of 45 patients, 34(76%) were females and 11(24%) were males with a male/female ratio of 3:1; while their age ranged between 28 and 72years with a mean of 57+15SD. All the patients were euthyroid and a quarter did not have symptoms apart from a neck mass. In all, 15% of the patients had recurrent goitre. CT scan of neck and chest was done in 31 (72%) patients; while 44 (98%) patients had cervical retrosternal goitres, 1(2%) patient had ectopic retrosternal goitre. A cervical incision was sufficient in 28 (62%) patients while 17 (38%) patients required additional sternotomy. Total thyroidectomy was done in all the patients. There were post-operative complications in 19 (42%) patients. Histopathology showed that 3(6.6%) patients had papillary thyroid carcinoma while 42(93.4%) had benign pathology findings. Conclusion: Surgical removal is the treatment of choice. Most retrosternal goitres can be resected through a collar stud incision; however the possibility of a need for a sternotomy should always be planned. The simultaneous occurrence of cervical and ectopic retrosternal goitre should always be ruled out with a CT scan.